Non-neoplastic colorectal disease biopsies: evaluation and differential diagnosis. Issue 12 (31st July 2020) - Moore, Michelle; Feakins, Roger M; Lauwers, Gregory Y
Abstract : A wide variety of non-neoplastic conditions may be encountered on colorectal biopsy encompassing idiopathic, infectious, vascular and immune-mediated aetiologies. Although interpretation of such biopsies may be challenging, appreciation of the dominant pattern of injury and subsequent host response may allow for a more focused histological diagnosis in the correct clinical and endoscopic setting. This article aims to provide a systematic, methodical approach to the assessment of such biopsies, concentrating mainly on diagnoses other than inflammatory bowel disease.